Why does college cost so much? - Archibald, Robert B., 1946-; Feldman, David Henry (New York ; Oxford : Oxford University Press, 2011)
College tuition has risen more rapidly than the overall inflation rate for much of the past century. To explain rising college cost, the authors place the higher education industry firmly within the larger economic history of the United States.
Includes bibliographical references and index.
Description based on print version record.
Keywords: College costs -- United States; Education, Higher -- United States -- Finance